PENGARUH MODEL CONTEXTUAL TEACHING AND LEARNING (CTL) BERBANTUAN MEDIA POP-UP BOOK TERHADAP KEMAMPUAN PEMAHAMAN MATEMATIS SISWA SEKOLAH DASAR - Alida Zia Fatimah; Erna Suwangsih; Primanita Sholihah Rosmana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is motivated by the low mathematical understanding ability of students because it is difficult to understand abstract concepts in mathematics. This study aims to determine the effect of the Contextual Teaching And Learning (CTL) learning model Assisted by Pop-Up Book Media on the Mathematical Understanding Ability of Elementary School Students. The research design used in this study is a quasi-experimental Non-Equivalent Control Group Design, and uses a purposive sampling technique. The sample numbered 28 in each experimental and control class. The data collection process used pretest and posttest instruments with descriptive and inferential analysis techniques. The results showed that the CTL model can improve students' mathematical understanding ability by 67.7% so it can be concluded that the CTL model is effective in improving students' mathematical understanding ability.